Legal Protection for Writers Against Violators of Illegal Copying of Books by Students - Eldon Rizky Hogantara; Nuria Siswi Enggarani (Universitas Muhammadiyah Surakarta, 2023)
Copyright is a piece of other intellectual property rights that continues to advance following the progress of an era that is very controlled from social, economic and technological aspects, because the more advanced technology a country is, the better the crimes committed. The progress of creative rights, which is supported by various elements, has an impact on improving legislative provisions in the copyright section. The rights that arise from a work in the field of science, according to the law, are delegated to the creator along with certain advantages, namely the right to explore his work. Meanwhile, in order to avoid crimes in the form of plagiarism or duplication, careful regulatory guidelines must be created and formulated in statutory regulations. A book is an intellectual work of the creator or copyright holder who has exclusive rights consisting of two rights, namely economic and moral rights, so these rights must be maintained. Due to the presence of exclusive rights, researchers are interested in knowing how to protect and the prospects for legal protection of copyright in internal knowledge books as regulated in Law NO 28 of 2014 concerning Copyright.